2023
DOI: 10.1039/d2nr05795f
|View full text |Cite
|
Sign up to set email alerts
|

Graphene nanoplatelets and other 2D-materials as protective means against the fading of coloured inks, dyes and paints

Abstract: The present work demonstrates the ability of graphene nanoplatelets (GNPs) and other two-dimensional materials (2DMs) like tungsten disulfide (WS2), molybdenum disulfide (MoS2) and hexagonal boron nitride (hBN) to act as...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 77 publications
(107 reference statements)
0
6
0
Order By: Relevance
“…Firstly, RGO formations were validated by GO's absorption peak shifting from 234 nm to 246 nm in RGO-AA/AuNPs spectrum and materialisation of RGO peak at 250 nm in RGO-DHA/AuNPs spectrum. These peaks correspond to π-π * transition related to C=C bond in an aromatic ring of the graphene and their observation is a strong indicator for RGO [18,22]. The intensity of RGO peak in figure 2(b) is comparatively smaller, implying that there are low percentage of RGO compared to sucrose precursor present in the measured sample.…”
Section: Characterisationmentioning
confidence: 90%
“…Firstly, RGO formations were validated by GO's absorption peak shifting from 234 nm to 246 nm in RGO-AA/AuNPs spectrum and materialisation of RGO peak at 250 nm in RGO-DHA/AuNPs spectrum. These peaks correspond to π-π * transition related to C=C bond in an aromatic ring of the graphene and their observation is a strong indicator for RGO [18,22]. The intensity of RGO peak in figure 2(b) is comparatively smaller, implying that there are low percentage of RGO compared to sucrose precursor present in the measured sample.…”
Section: Characterisationmentioning
confidence: 90%
“…Additionally, Kotsidi et al demonstrated that the use of graphene and GRMs as additives in inks and paints hinders fading effects with a protection factor reaching ≈40% (Figure 3B). [116] The authors identified different mechanisms of action for the different types of graphene adopted. Graphene nanoplatelets act thanks to the synergy between two main actions: preventing oxidation due to the absorption of the radiation in the UV range and scavenging free radicals, such as OH • .…”
Section: Graphene Protection Against Color Fadingmentioning
confidence: 99%
“…Importantly, these values are also much larger than the maximal strain reported for silicon (∼2%) and larger than the maximal strain of polydimethylsiloxane (PDMS) and polyimide (PI) (∼7%) that are commonly used in flexible electronics. Recent studies demonstrated that the stretchability of 2D materials is attractive for many high-end applications, including flexible photodetectors, 56 electronic skin, 57 strain sensors, 58 and stretchable transistors. 59 Thus, the outstanding stretchability of ReS 2 and ReSe 2 alongside its optoelectronic properties makes them promising candidate materials for advanced flexible devices.…”
Section: Papermentioning
confidence: 99%